Asymmetric sensorineural hearing loss and vestibular schwannoma: when to image?. Issue 5 (October 2020) - Conley, Morgan; Diaz, Rodney C.
Abstract : Purpose of review: We review the literature on the use of audiometric protocols in the guidance of when to obtain MRI for detection of vestibular schwannoma. This discussion will focus on the sensitivity, specificity, and cost-effective analysis of audiometric criteria of asymmetric sensorineural hearing loss (ASNHL) when used to decide when MRI scans should be performed. Recent findings: The sensitivity for detecting vestibular schwannomas when invoking published audiometric protocols for triggering MRI acquisition in ASNHL ranged from 50 to 100%. Specificity of these protocols ranged from 23 to 83%. Such audiometric protocols are efficient, achieving sensitivity and specificity at these rates while reducing the screening rate to 18 to 35%. The reduced procurement of MRI while using such audiometric protocols is associated with annual cost savings of between 23 and 82%. While no definitive recommendations can be made from this review, some audiometric protocols offer a better balance of sensitivity and specificity than others. Summary: Audiometric protocols for triggering MRI acquisition in ASNHL for evaluation of vestibular schwannoma can be both sensitive and specific. These are competitive measures, and so no protocol is both 100% sensitive and specific. Such protocols become less effective in populations with increased incidence of noise-induced hearing loss. Invocation of such audiometric protocols can considerably reduce the annual cost of MRI evaluation for vestibular schwannomas.